1998
DOI: 10.1007/s005920050123
|View full text |Cite
|
Sign up to set email alerts
|

Electronegative low density lipoprotein subform (LDL - ) is increased in type 2 (non-insulin-dependent) microalbuminuric diabetic patients and is closely associated with LDL susceptibility to oxidation

Abstract: There is increasing evidence that diabetes mellitus is characterized by an enhanced lipoprotein oxidation. We have therefore investigated whether a relationship exists between LDL oxidation and microalbuminuria, which is considered an early marker of vascular involvement in type 2 diabetic patients. We selected 12 microalbuminuric and 12 normoalbuminuric type 2 diabetic patients, and 12 control subjects comparable for age, sex and blood pressure values. Oxidatively modified plasma LDL, referred as LDL-, were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 0 publications
1
21
0
2
Order By: Relevance
“…In accordance with this, we recently demonstrated that free (unesterified) 7-ketocholesterol levels are significantly higher in the LDL of patients with well-controlled type 2 diabetes than in the LDL of healthy subjects [53]. Furthermore, it has been shown that the percentage of electronegative LDL in plasma is higher in microalbuminuric diabetic patients than in normoalbuminuric diabetic patients or control subjects [67]. Plasma levels of oxidised LDL, as measured by sandwich ELISA, were increased in individuals with IGT compared with control subjects after adjusting for age and BMI [68], and are higher in type 2 diabetic patients with macroalbuminuria than in patients with normo-or microalbuminuria or healthy control subjects [69].…”
Section: Measurement Of Ldl Oxidationsupporting
confidence: 58%
“…In accordance with this, we recently demonstrated that free (unesterified) 7-ketocholesterol levels are significantly higher in the LDL of patients with well-controlled type 2 diabetes than in the LDL of healthy subjects [53]. Furthermore, it has been shown that the percentage of electronegative LDL in plasma is higher in microalbuminuric diabetic patients than in normoalbuminuric diabetic patients or control subjects [67]. Plasma levels of oxidised LDL, as measured by sandwich ELISA, were increased in individuals with IGT compared with control subjects after adjusting for age and BMI [68], and are higher in type 2 diabetic patients with macroalbuminuria than in patients with normo-or microalbuminuria or healthy control subjects [69].…”
Section: Measurement Of Ldl Oxidationsupporting
confidence: 58%
“…11,12 High concentrations of LDL(Ϫ) have been associated with major risk factors for cardiovascular disease, including hypercholesterolemia 13 and type 2 diabetes mellitus. 14 Apparently more toxic still is L5, which is the most electronegative of the LDL subfractions separable by highcapacity ion-exchange chromatography according to charge that we first described in 2003. 11,15 L5 is present in hypercholesterolemic subjects and those with type 2 diabetes but not in healthy subjects with clinically normal lipid concentrations.…”
mentioning
confidence: 99%
“…Plasma LDL(2) is increased in subjects at high risk for cardiovascular disease as a result of hypercholesterolemia (10)(11)(12), hypertriglyceridemia (11,13), diabetes (14)(15)(16)(17), or coronary artery disease (18). Simvastatin therapy reduces the proportion of LDL(2) without modifying its oxidizability (12).…”
mentioning
confidence: 99%